The Impact of Group Diversity and Structure on Individual Negative Workplace Gossip. Issue 1 (1st January 2021) - Kim, Andrea; Shin, Jiseon; Kim, Youngsang; Moon, Jinhee
ABSTRACT: This study examines how group diversity affects individual group members' negative gossip about their colleagues and how this linkage is altered by group structure. We hypothesize that group diversity in terms of organizational tenure reduces individual negative gossip about coworkers, and that the diversity–gossip linkage is moderated by a self-managing structure. With a multi-source dataset collected from 312 nurses employed in 39 nursing groups at four healthcare organizations, our random coefficient modeling analysis revealed that employees in groups with high tenure diversity are less likely to negatively gossip about their coworkers when the group has a greater self-managing structure. This study provides theoretical implications pertaining to the contextual influences on workplace gossip. Our findings offer practical implications regarding the management of employee gossip at work.